Perspectives on electronic medical records adoption: electronic medical records (EMR) in outcomes research - Belletti, Dan (Dove Medical Press, 2010)
Health information technology (HIT) is engineered to promote improved quality and efficiency of care, and reduce medical errors. Healthcare organizations have made significant investments in HIT tools and the electronic medical record (EMR) is a major technological advance. The Department of Veterans Affairs was one of the first large healthcare systems to fully implement EMR. The Veterans Health Information System and Technology Architecture (VistA) began by providing an interface to review and update a patient’s medical record with its computerized patient record system. However, since the implementation of the VistA system there has not been an overall substantial adoption of EMR in the ambulatory or inpatient setting. In fact, only 23.9% of physicians were using EMRs in their office-based practices in 2005. A sample from the American Medical Association revealed that EMRs were available in an office setting to 17% of physicians in late 2007 and early 2008. Of these, 17% of physicians with EMR, only 4% were considered to be fully functional EMR systems. With the exception of some large aggregate EMR databases the slow adoption of EMR has limited its use in outcomes research. This paper reviews the literature and presents the current status of and forces influencing the adoption of EMR in the office-based practice, and identifies the benefits, limitations, and overall value of EMR in the conduct of outcomes research in the US.